[PP.23.08] PREVALENCE OF RESISTANT HYPERTENSION IN THE ELDERLY HYPERTENSIVE SUBJECTS - THE RESULTS OF THE POPULATION-BASED STUDY 'POLSENIOR'. (September 2016) - Wizner, B.; Siga, O.; Zdrojewski, T.; Wiecek, A.; Chudek, J.; Mossakowska, M.; Walczewska, J.; Slusarczyk, P.; Bandosz, P.; Grodzicki, T.
Abstract : Objective: The aim of the study was to assess the prevalence of drug-resistant hypertension among Polish elderly population. Design and method: The cross-sectional, population-based survey PolSenior was performed on random sample of elderly subjects (years: 2007–2011). Of 4979 subjects aged 65 years (range: 65 to 104), 3100 subjects taking the antihypertensive medications or untreated hypertensive subjects with uncontrolled blood pressure (BP=>140/90 mmHg) were included to the analysis. Resistant hypertension (RHT) was defined as the uncontrolled hypertension despite taking 3 or more medications each one from different drug classes. The used definition of RHT was not include the requirement of a diuretic. Results: Mean age of the subjects was 78.8 ± 8.4 yrs, 51.1% were women. The prevalence of RHT was 8.7% (Figure 1) and it tended to be more prevalent in younger than in very old subjects (P for trend = 0.058). Compared with the subjects with controlled hypertension using 3 or more medications from different drug classes, the elderly subjects with RHT tended to be younger (79.3 vs 77.9 yrs, P = 0.053) and much less likely treated with diuretic (51.9% vs 24.7%, P < 0.001). The subjects with RHT did not differ in the proportion of taking a thiazide or thiazide like diuretics but were much rarely treated with an aldosterone receptor antagonists (51.9% vs 24.7%, P < 0.001) or loop diuretics (31.4% vs 18.6%, P < 0.001). Figure. No caption available. Figure 1. Proportions (and numbers) of subjects in the PolSenior survey with different levels of BP control and treatment intensities. Conclusions: The prevalence of RHT in population seems to be relatively low but it is difficult to estimate it precisely due to the problems with the definition of RHT, clear classification of subjects with hypertension as well as establishing the adherence level in the uncontrolled patients. Nonetheless, our data from the elderly population correspond with the results of the NHANES study 2003–2008), as well as the recently published data from the metaanalysis (Achelrod D. et al. Am J Hypertens 2015). The further analyses are needed to assess the true resistant hypertension with the requirement of usage of diuretic, especially an aldosterone receptor antagonists.